shp-2 gene knockout upregulates CAR-driven cytotoxicity of YT NK cells - V. G. Subrakova; S. V. Kulemzin; T. N. Belovezhets; A. N. Chikaev; N. A. Chikaev; O. A. Koval; A. A. Gorchakov; A. V. Taranin (Вавиловский журнал генетики и селекции)
In Russia, cancer is the second leading cause of death following cardiovascular diseases. Adoptive transfer of NK cells is a promising approach to fight cancer; however, for their successful use in cancer treatment, it is necessary to ensure their robust accumulation at tumor foci, provide resistance to the immunosuppressive tumor microenvironment, and to engineer them with higher cytotoxic activity. NK lymphocytes are known to kill cancer cells expressing a number of stress ligands; and the balance of signals from inhibitory and activating receptors on the surface of the NK cell determines whether a cytotoxic reaction is triggered. We hypothesized that stronger cytotoxicity of NK cells could be achieved via gene editing aimed at enhancing the activating signaling cascades and/or weakening the inhibitory ones, thereby shifting the balance of signals towards NK cell activation and target cell lysis. Here, we took advantage of the CRISPR/Cas9 system to introduce mutations in the coding sequence of the shp-2 (PTPN11) gene encoding the signaling molecule of inhibitory pathways in NK cells. These shp-2 knock-out NK cells were additionally transduced to express a chimeric antigen receptor (CAR) that selectively recognized the antigen of interest on the target cell surface and generated an activating signal. We demonstrate that the combination of shp-2 gene knockout and CAR expression increases the cytotoxicity of effector NK-like YT cells against human prostate cancer cell line Du-145 with ectopic expression of PSMA protein, which is specifically targeted by the CAR.